Guaranteeing positive destinations for youth in a Danish municipality: the transfer, translation, and transformation of a policy instrument. (January 2023) - Friche, Nanna; Enemark, Nanna Ramsing; Ydesen, Christian
In 2019, Hjørring Municipality launched a comprehensive Youth Guarantee programme to ensure 'positive destinations' for the municipality's youth. The strategy was explicitly inspired by Edinburgh's interpretation of the Scottish Youth Guarantee. In this article, we conceptualize the Youth Guarantee as a policy instrument and unpack the transfer, translation, and transformation from the initial coincidental inspiration to the policy instrument developing a 'life of its own'. The instrument serves as a vehicle for creating a constituency centred on a value-based governing paradigm, alliances, and the enthusiastic spread of the Youth Guarantee spirit. The case serves as an example of how the transfer, translation, and transformation processes of a policy instrument into a foreign legal context can play out, as well as how dominating forms of governance centred on values, alliances, and common enthusiasm in the constituency – and even the contours of a governance paradigm – can be teased out through such an endeavour.